Useful strength in badminton, volley, tennis and handball: comparison by means of the Atlas tests - Blasco-Lafarga, C.; Garrido Chamorro, R. P.; Albert Gimenez, A. R. (Archivos de medicina del deporte, 2008)
The aim of this study is to analyse the differences found in the Useful Strength of the main technical movements in four different sports: (Badminton, Tennis, Volleyball and Handball). Material and methods: We have assessed the Useful Strength in 39 athletes (8 tennis, 10 badminton, 15 handball and 6 volleyball players), analysing: time of acceleration (Tace), maximum force (Fmax), ascending hypotenuse (HASCO), alpha angle (Alpha), beta angle (Beta) and Rate Force Development (RFD), measured by means of the Atlas and applying the triangulation method. The entire tests were developed with specific technical movements. Results: The mean values for each sport were: Tace was 0.17 seconds (sec) for badminton, 0.20 sec for Tennis, 0.47 sec for handball and 0.27 sec for volleyball; Fmax was 36.01 Newton (N) for badminton, 63.79 N for tennis, 91.04 N for handball and 63.26 N for volleyball; HASCO was 40.39 N/sec for badminton, 67.45 N/sec for tennis, 103.7 N/sec for handball and 69.56 N/sec for volleyball; Angle Alpha was 63.90° for badminton, 71.63º for tennis, 62.52º for handball and 65.41º for volleyball; Angle Beta was 26.08° for badminton, 18.27º for tennis, 27.48º for handball and of 24.5º for volleyball; and RFD was 204.76 N/sec for badminton, 331.1 N/sec for tennis, 196.59 N/sec for handball and 233.9 N/sec for volleyball. We have found significant differences p <0.001 in all the comparatives. Conclusions: Values, time to peak force, RFD and profile in which we apply the maximum production of force, are different depending on the sport. These four sports have their own useful strength pattern; a determining factor which conditions a different training planning that must be adapted to the specific requirements. The Useful Strength is a multifactorial conditioning factor, mainly specific and technical, and so should be trained.